2008
DOI: 10.1089/neu.2008.0625
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive Craniectomy as the Primary Surgical Intervention for Hemorrhagic Contusion

Abstract: The standard surgical treatment of hemorrhagic cerebral contusion is craniotomy with evacuation of the focal lesion. We assessed the safety and feasibility of performing decompressive craniectomy and duraplasty as the primary surgical intervention in this group of patients. Fifty-four consecutive patients with Glasgow Coma Scale (GCS) scores of less than or equal to 8, a frontal or temporal hemorrhagic contusion greater than 20 cm(3) in volume, and a midline shift of at least 5 mm or cisternal compression on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 25 publications
1
51
0
1
Order By: Relevance
“…A few additions have also been made to the list of available treatment options with the most noteworthy being endoscopic third ventriculostomy The median time from shunt placement to first shunt failure noted in our study was 22.5 days, which is comparable to that reported by other studies (12,14). As mentioned previously, the development of hydrocephalus following cranial surgery (29) may be attributed to the direct collateral damage incurred during the surgical procedure (19). Theoretically, therefore, the indication for which cranial surgery was performed, the expertise of the operating surgeon, the surgical techniques employed as well as other patient factors may influence the survival of VP shunts placed in such patients.…”
Section: █ Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A few additions have also been made to the list of available treatment options with the most noteworthy being endoscopic third ventriculostomy The median time from shunt placement to first shunt failure noted in our study was 22.5 days, which is comparable to that reported by other studies (12,14). As mentioned previously, the development of hydrocephalus following cranial surgery (29) may be attributed to the direct collateral damage incurred during the surgical procedure (19). Theoretically, therefore, the indication for which cranial surgery was performed, the expertise of the operating surgeon, the surgical techniques employed as well as other patient factors may influence the survival of VP shunts placed in such patients.…”
Section: █ Discussionsupporting
confidence: 85%
“…In our study, patients who developed hydrocephalus following cranial surgery performed for brain tumors had a significantly decreased median time to first shunt failure. This may be explained by the extensive manipulation and injury to tissues incurred during resection of neoplastic disease as well as the alterations in cerebral blood flow and auto-regulation that develops after the procedure (19,29,46,47).…”
Section: █ Discussionmentioning
confidence: 99%
“…The size of the dural incision was generally no greater than 5 mm, which was often the size of the diameter of the aspirator head. After the dural incision was made, the aspirator head was placed into the incision, the hematoma was partially aspirated, the contused tissue was slowly aspirated, and ICP was gradually Although this approach has been reported to effectively reduce ICP and improve prognoses in some studies (1,2,7,8), the findings from a recent multinational randomized trial indicate that decompressive craniectomy may be associated with worse outcomes, as indicated by 6-month extended Glasgow Outcome Scale (GOS) scores, compared with standard care in patients with severe head injury (2). The authors of the report suggested that neural injury and alterations in cerebral blood flow and metabolism may have contributed to the worse outcome with decompressive craniectomy (2).…”
Section: Controlled Decompressionmentioning
confidence: 99%
“…The hematoma volume was graded on a 10-point scale. With regards to injury/surgery time interval, previous studies have shown that the longer the time interval between injury and surgery, the greater the swelling and intracranial pressure (16,32); thus, a 10-point scale was set that ranged from 1 to 8 hours, with a longer time interval leading to a lower score, as this lowered the likelihood of preserving bone flap (undergoing the CR procedure instead of DC) (12). For the injury/surgery time interval category, we also took into consideration the uneven time distribution when designing the scale to make it more reasonable.…”
Section: Methodsmentioning
confidence: 99%